The role of protein methyltransferases as potential novel therapeutic targets in squamous cell carcinoma of the head and neck. (June 2018) - Saloura, Vassiliki; Vougiouklakis, Theodore; Sievers, Cem; Burkitt, Kyunghee; Nakamura, Yusuke; Hager, Gordon; van Waes, Carter
Highlights: The TCGA has revealed a plethora of genetic and expression alterations in protein methyltransferases in SCCHN. Functions of protein methyltransferases include immune evasion, cancer stemness and activation of signaling pathways. Methylation substrates are not only histones but also non-histone proteins, such as the epidermal growth factor receptor. Protein methyltransferases show a promising potential as the next generation of therapeutic targets in SCCHN. Abstract: Squamous cell carcinoma of the head and neck is a lethal disease with suboptimal survival outcomes and standard therapies with significant comorbidities. Whole exome sequencing data recently revealed an abundance of genetic and expression alterations in a family of enzymes known as protein methyltransferases in a variety of cancer types, including squamous cell carcinoma of the head and neck. These enzymes are mostly known for their chromatin-modifying functions through methylation of various histone substrates, though evidence supports their function also through methylation of non-histone substrates. This review summarizes the current knowledge on the function of protein methyltransferases in squamous cell carcinoma of the head and neck and highlights their promising potential as the next generation of therapeutic targets in this disease.